Application of Components of the Massachusetts' Sports Concussion Regulations to All Students With Concussion: A Survey of School Nurses. (August 2020) - Hackman, Holly; Howland, Jonathan; Taylor, Alyssa; Brown, Linda; Gapinski, Mary Ann; Olshaker, Jonathan; Stern, Robert A.
Appropriate management by schools of all students with a concussion, regardless of the cause, has not received the same attention as sports-related concussions. Focus groups conducted with Massachusetts School Nurses in 2015 found that some had applied protocols required in the state's sports concussion regulations to all students with concussion, not just student athletes. We surveyed high school nurses in Massachusetts to examine (1) the extent of this practice and (2) the extent to which protocols for all students with concussion are included in school policies. Of 168 (74%) responding, 94% applied the return-to-learn and play, and medical clearance requirements to all students with concussion, regardless of how or where the concussion occurred and 77% reported their school's policy required these protocols for all students with concussion. A significant association (odds ratio: 13.3, 95% confidence interval [2.4, 72.8], p <.01) existed between the two measures. These findings have important clinical and academic implications.